2020
DOI: 10.3389/fimmu.2020.575818
|View full text |Cite
|
Sign up to set email alerts
|

The Human-Specific STING Agonist G10 Activates Type I Interferon and the NLRP3 Inflammasome in Porcine Cells

Abstract: Pigs have anatomical and physiological characteristics comparable to those in humans and, therefore, are a favorable model for immune function research. Interferons (IFNs) and inflammasomes have essential roles in the innate immune system. Here, we report that G10, a human-specific agonist of stimulator of interferon genes (STING), activates both type I IFN and the canonical NLRP3 inflammasome in a STING-dependent manner in porcine cells. Without a priming signal, G10 alone transcriptionally stimulated Sp1-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
(75 reference statements)
1
8
0
Order By: Relevance
“…Third, in response to cytosolic DNA in human myeloid cells, the CGAS-STING1 pathway instead of AIM2 activates potassium efflux-mediated NLRP3 inflammasome via lysosomal STING1-mediated lysosomal cell death 147 . Consistent with this, G10 (an agonist of STING1) induces potassium efflux and NLRP3 activation in porcine cells 148 . Conversely, the inhibition of NLRP3 inflammasomes increases STING1-dependent IFN production 148 , while the activation of NLRP3 or AIM2 in murine macrophages leads to the inactivation of the STING1 pathway 149 , 150 , suggesting a yet unknown mechanism to balance the activation of STING1 and inflammasomes in response to infection.…”
Section: Sting1 In Cell Deathsupporting
confidence: 60%
“…Third, in response to cytosolic DNA in human myeloid cells, the CGAS-STING1 pathway instead of AIM2 activates potassium efflux-mediated NLRP3 inflammasome via lysosomal STING1-mediated lysosomal cell death 147 . Consistent with this, G10 (an agonist of STING1) induces potassium efflux and NLRP3 activation in porcine cells 148 . Conversely, the inhibition of NLRP3 inflammasomes increases STING1-dependent IFN production 148 , while the activation of NLRP3 or AIM2 in murine macrophages leads to the inactivation of the STING1 pathway 149 , 150 , suggesting a yet unknown mechanism to balance the activation of STING1 and inflammasomes in response to infection.…”
Section: Sting1 In Cell Deathsupporting
confidence: 60%
“…Conversely, stimulation of the cGAS-STING pathway is a novel approach to immune activation in cancer immune-therapy. Small-molecule STING agonists have been used to activate the cGAS-STING pathway and promote antitumor immunity ( 68 76 ). Additional work indicates STING agonists are effective in combinatorial therapies for infection ( 77 ).…”
Section: Cgas and Sting As Therapeutic Targetsmentioning
confidence: 99%
“…Studies have reported four possible models [K + efflux, lysosomal damage, reactive oxygen species (ROS) and Ca 2+ mobilization] ( 20 ) for NLRP3 inflammasome activation ( Fig. 1 ), which may not be exclusive.…”
Section: Biology Of the Nlrp3 Inflammasomementioning
confidence: 99%